TACE-assisted multi-image guided radiofrequency ablation for the treatment of single hepatocellular carcinoma ≤ 5 cm: a retrospective study - Xie, Yong; Lyu, Tianshi; Song, Li; Tong, Xiaoqiang; Wang, Jian; Zou, Yinghua (Frontiers in Oncology, 2024)
Background/Objective: Treatment of hepatocellular carcinoma (HCC) with ablation alone often results in high rates of recurrence and metastasis, reaching up to 25.9% within two years. Therefore, this study aimed to examine the efficacy and safety of transarterial chemoembolization (TACE)-assisted multi-image guided radiofrequency ablation (RFA) for the treatment of stage Ia HCC according to the China liver cancer staging (CNLC).Methods: This study enrolled and analyzed a total of 118 patients diagnosed with HCC, each with a single nodular lesion no larger than 5 cm, who received TACE-RFA as first-line therapy between February 1, 2014, and December 31, 2021. The median/mean follow-up period was 29.0 months [95% confidence interval (CI): 21.8-36.2 months] and 31.8 months (95% CI: 27.5-36.0 months), respectively. We assessed the treatment's effectiveness, potential complications, and survival rate.Results: The technical success rate was 100% (118/118) after the initial treatment. Out of the total, 3 out of 118 patients (2.5%) developed local tumor progression (LTP) during the follow-up period. The median time for LTP was 29.0 months (95%CI: 21.9-36.1 months; mean: 31.5 months; range 1-92 months). At 1, 3, 5, and 7 years after treatment, the cumulative LTP rates were 0%, 4.6%, 4.6%, and 4.6%, respectively. The overall survival rates at 1, 3, 5, and 7 years were 100%, 95.2%, 95.2%, and 95.2%, respectively. In total, 28 patients experienced minor Grade B complications, and no major complications or treatment-related mortality occurred.The treatment of CNLC stage Ia HCC using TACE-assisted multi-image-guided RFA was found to be both safe and feasible.